Nutrition and Lifestyle Aspects of the Elderly - Pumputienė, Ingrida; Damulevičienė, Gytė; Lisauskaitė, Gabrielė; Petereit, Rūta; Lenkutienė, Dalia; Maksimova, Laura; Pliupelis, Marius; Barčytė, Rasa; Laurinaitis, Jonas; Rimeikaitė, Skaistė; Jonušienė, Rasa (Slauga. Mokslas ir praktika, 2024)
Theses of the Presentations at the Conference (March 15, 2024) Organized by theLithuanian Society of Dietitians and the Health Care Faculty of Vilnius College